2022
DOI: 10.1186/s12903-022-02432-7
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 as an opportunity for minimally-invasive dentistry: a national cross-sectional survey

Abstract: Background During the COVID19 pandemic, the Latvian government issued first absolute restrictions (elective treatments prohibited, only emergency care) and later relative restrictions (preference for non-aerosol-generating procedures (AGP) and emergency care) on dental care. This study aims to assess the impact of these restrictions on the decision made by Latvian dentists about caries treatment. Methods A Survey-based cross-sectional study was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The results of our study, along with the increased interest in non-invasive treatments during the COVID-19 pandemic 22 , suggest that the use of SDF could be a valuable addition to caries management protocols. The national survey of Latvian dentists 22 showed a general openness to incorporating non-invasive treatments, such as SDF.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The results of our study, along with the increased interest in non-invasive treatments during the COVID-19 pandemic 22 , suggest that the use of SDF could be a valuable addition to caries management protocols. The national survey of Latvian dentists 22 showed a general openness to incorporating non-invasive treatments, such as SDF.…”
Section: Discussionmentioning
confidence: 78%
“…The results of our study, along with the increased interest in non-invasive treatments during the COVID-19 pandemic 22 , suggest that the use of SDF could be a valuable addition to caries management protocols. The national survey of Latvian dentists 22 showed a general openness to incorporating non-invasive treatments, such as SDF. Nevertheless, there is a need to find the best way to get the uptake of these treatments by dentists, which might include better dissemination of information, hands-on training, and reliable evidence to support their use and offer them to parents.…”
Section: Discussionmentioning
confidence: 78%
“…The results of our study, along with the increased interest in non-invasive treatments during the COVID-19 pandemic 22 , suggest that the use of Silver Diammine Fluoride (SDF) could be a valuable addition to caries management protocols. The national survey of Latvian dentists 22 showed a general openness to incorporating non-invasive treatments, such as SDF.…”
Section: Discussionmentioning
confidence: 95%
“…Sample size was calculated based on the study by Maldupa and Uribe [2021], which aimed to assess the impact of government restrictions about aerosol-generating procedures on the decision made by dentists about caries treatment. Using the Qui-square test with contingency tables, data regarding the difference of proportion between dentists who chose or not the use of aerosol-generating procedures for carious lesion treatments were applied.…”
Section: Sample Sizementioning
confidence: 99%
“…Since some studies showed that COVID-19 pandemic may have influenced professionals in all parts of the world to adopt minimally invasive techniques more frequently [Alamoudi et al, 2022;Maldupa et al, 2022], we raised the hypothesis that Brazilian dentists could also be influenced by COVID-19 and were favored to practice some minimally invasive techniques to manage dental caries regularly. Therefore, this study aimed to evaluate, through an online questionnaire, changes in the attitudes of Brazilian dentists related to the frequency of use of MI caries management considering the periods before and during the COVID-19 pandemic since a great indication of MI techniques during the pandemic period has been encouraged in all parts of the world.…”
Section: Introductionmentioning
confidence: 99%